Effects of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers on Angiotensin-Converting Enzyme 2 Levels: A Comprehensive Analysis Based on Animal Studies - Kriszta, Gábor; Kriszta, Zsófia; Váncsa, Szilárd; Hegyi, Péter Jenő; Frim, Levente; Erőss, Bálint; Hegyi, Péter; Pethő, Gábor; Pintér, Erika (Frontiers in Pharmacology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the pathogen of coronavirus disease 2019 (COVID-19), caused the outbreak escalated to pandemic. Reports suggested that near 3% of COVID-19 cases have a fatal outcome. Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are widely used in hypertension, heart failure and chronic kidney disease. These drugs have been reported to upregulate angiotensin-converting enzyme 2 (ACE2), which produces Ang (1–7), the main counter-regulatory mediator of angiotensin II. This enzyme is also known as the receptor of SARS-CoV-2 promoting the cellular uptake of the virus in the airways, however, ACE2 itself proved to be protective in several experimental models of lung injury. The present study aimed to examine the relationship between ACEI/ARB administration and ACE2 expression. After a comprehensive search and selection, 27 animal studies investigating ACE2 expression in the context of ACEI and ARB were identified. The majority of these papers reported increased ACE2 levels in response to ACEI/ARB treatment. This result should be interpreted in the light of the dual role of ACE2 being a promoter of viral entry to cells and a protective factor against oxidative damage in the lungs.